Performance Investigation and Tuning in the Interoperable Cloud4E Platform - Limmer, Steffen; Fey, Dietmar; et al. (Euro-Par 2014 Workshop, Part II, 2014)
The paradigm of Software as a Service (SaaS) offers an interesting option to vendors of simulation software for providing their applications to a wide circle of customers. However, this imposes a challenge to vendors whose applications exist only as classical desktop tools, so far: Interfaces for the remote control have to be provided which are as independent from the underlying cloud infrastructure as possible in order to avoid vendor lock-ins. We present an interoperable platform developed in the project Cloud4E (Trusted Cloud Computing for Engineering), which allows the provisioning of existing simulation software in form of a service in a cloud. The interoperability of the platform and of the services is achieved by the usage of the Open Cloud Computing Interface (OCCI) together with the Advanced Message Queuing Protocol (AMQP) where OCCI is not only used as interface to Infrastructure as a Service (IaaS) but also as interface to SaaS. Hence, the OCCI server plays a central role within the platform and can quickly become a bottleneck, which degrades the performance of the whole platform. We present detailed performance investigations and suggest options to improve the performance. The investigations were performed on the widely used OCCI server implementation called rOCCI server connected to the OpenNebula cloud middleware.
UnivIS-Import:2015-04-16:Pub.2014.tech.IMMD.IMMD3.perfor
Keywords: CAE; Cloud; Cloud4E; OCCI; OpenNebula; ROCCI server